International radio broadcasting – a case of Radio Poland – an external service of Polish public radio. - Wielopolska-Szymura, Mirosława (Political Preferences, 2018)
Since its beginning radio has also been used as an instrument of international communication. Broadcast stations sending messages abroad began to appear shortly after the first wireless transmissions were successfully performed with the use of the Morse code. The discovery of radio waves enabled sending information on long distances without wire. This invention gave the new possibilities to communicate between continents, from ships to shores and back, or between military troupes during wartime. International broadcasting was also used to communicate with allies and with enemies during military conflicts. At that time an ability to transmit voice using radio waves had already been developed, then radio transmissions entered the dimension of entertainment as well as political communication with citizens and foreigners. The international voice broadcasting service has been developed from 1927 with the purpose of keeping the citizens in touch with the mother countries and also of helping the governments to disseminate its culture throughout the world. In this context the article is an analysis of the legal basis, purposes, directions and technical aspects of broadcasting, and organisational structure of the Radio Poland (former Polish Radio External Service). Key words: international broadcasting, radio broadcasting, Radio Poland, Polish Radio External Service, short waves